Sendai virus M protein binds independently to either the F or the HN glycoprotein in vivo. - Sanderson, C M (1994)
We have analyzed the mechanism by which M protein interacts with components of the viral envelope during Sendai virus assembly. Using recombinant vaccinia viruses to selectively express combinations of Sendai virus F, HN, and M proteins, we have successfully reconstituted M protein-glycoprotein interaction in vivo and determined the molecular interactions which are necessary and sufficient to promote M protein-membrane binding. Our results showed that M protein accumulates on cellular membranes via a direct interaction with both F and HN proteins. Specifically, our data demonstrated that a small fraction (8 to 16%) of M protein becomes membrane associated in the absence of Sendai virus glycoproteins, while > 75% becomes membrane bound in the presence of both F and HN proteins. Selective expression of M protein together with either F or HN protein showed that each viral glycoprotein is individually sufficient to promote efficient (56 to 73%) M protein-membrane binding. Finally, we observed that M protein associates with cellular membranes in a time-dependent manner, implying a need for either maturation or transport before binding to glycoproteins.